Strategi Peningkatan Daya Saing Produk Suku Cadang Otomotif dan Elektonik Berbahan Karet di PT BesQ Sarana Abadi - Hanafi, Imron; Hubeis, Aida Vitayala S; Raharja, Sapta (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
In order to spur the automotive and electronic industries to meet domestic needs and compete in the era of globalization, the development of manufacturing industries is not only based on large-scale industries, but also needs to be developed into Small and Medium Enterprises (SMEs). The obstacles faced today are limited capital, human resources (HR), product development and marketing procedures. PT BesQ Sarana Abadi is a small and medium business (UKM) engaged in the business of making rubber parts. In order to improve competitiveness, PT BesQ Sarana Abadi is researched with the formulation of the right competitiveness strategy. The objectives of the study are: (1) to identify factors that influence the competitive advantage of rubber and automotive parts products; (2) analyzing internal and external factors that affect the competitiveness of rubber and automotive parts industry products using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) methods; (3) develop competitiveness strategies for the automotive and electronic spare parts products industry using Internal-External (IE) methods and Strengths, Weakness, Opportunities, Threats (SWOT) and Balance Score Cards (BSC); (4) formulating priority strategies to improve the competitiveness of rubber and automotive parts industry products using the Quantitative Strategic Planning Matrix (QSPM) method. From the analysis results, there are many weaknesses in the company. In this case a high opportunity value causes the company to operate, because in the IFE matrix the value of strength is greater than the value of weakness. In the EFE matrix, the opportunity value is greater than the threat. With the SWOT and BSC methods identified strategies needed, set the priority of the strategy by using the QSPM method.